2023
DOI: 10.1002/anie.202312163
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Electrochemical CO2 Reduction on Copper by Reactive Ionic Liquid and Native Hydrogen Bond Donors

Oguz Kagan Coskun,
Saudagar Dongare,
Brian Doherty
et al.

Abstract: Electrochemical CO2 reduction (CO2RR) on copper (Cu) shows promise for higher‐value products beyond CO. However, challenges such as the limited CO2 solubility, high overpotentials, and the competing hydrogen evolution reaction (HER) in aqueous electrolytes hinder the practical realization. We propose a functionalized ionic liquid (IL) which generates ion‐CO2 adducts and a hydrogen bond donor (HBD) upon CO2 absorption to modulate CO2RR on Cu in a non‐aqueous electrolyte. As revealed by transient voltammetry, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This shift underscores the necessity of comprehensively understanding the mechanisms of CO 2 binding and the processes away from the equilibrium as the dynamic nature of the interface presents an electron transfer reaction in parallel to other chemical reactions such as hydrogen transfer among the IL ions and CO 2 chemisorption by both the anion and the cation. Recently, we reported on the reduction of the onset potential of CO 2 RR on Ag and Cu electrodes with a CO 2 -reactive [EMIM]­[2-CNpyr] IL in non-aqueous electrolyte where the microenvironment and the catalytic role of the IL were examined through the interfacial structure and surface species as investigated by EIS and in situ SERS. While CO was obtained as the only product over Ag (>95% Faradaic efficiency), various C 2+ products were reported over Cu owing to the stabilization of the reaction intermediates on the electrode surface and the hydrogen bonding among the interfacial species.…”
Section: Significance Of the Electrode–electrolyte Interface In Energ...mentioning
confidence: 99%
“…This shift underscores the necessity of comprehensively understanding the mechanisms of CO 2 binding and the processes away from the equilibrium as the dynamic nature of the interface presents an electron transfer reaction in parallel to other chemical reactions such as hydrogen transfer among the IL ions and CO 2 chemisorption by both the anion and the cation. Recently, we reported on the reduction of the onset potential of CO 2 RR on Ag and Cu electrodes with a CO 2 -reactive [EMIM]­[2-CNpyr] IL in non-aqueous electrolyte where the microenvironment and the catalytic role of the IL were examined through the interfacial structure and surface species as investigated by EIS and in situ SERS. While CO was obtained as the only product over Ag (>95% Faradaic efficiency), various C 2+ products were reported over Cu owing to the stabilization of the reaction intermediates on the electrode surface and the hydrogen bonding among the interfacial species.…”
Section: Significance Of the Electrode–electrolyte Interface In Energ...mentioning
confidence: 99%
“…The electrocatalytic reaction occurs in the narrow nanoscale region at the electrode–electrolyte interface. Modifying the components of electrolytes is a significant strategy to regulate the interfacial hydrogen-bond (H-bond) environment and steer the kinetics of hydrogen-related reactions, e.g., HER and CO 2 RR. For instance, Li et al discovered that alkali-metal cations can modulate proton transfer kinetics by reducing the connectivity of the H-bond network in the electric double layer (EDL) . Xu and co-workers demonstrated that bulky organic cations, such as tetrapropyl ammonium, can foster the formation and lifetime of H-bonds among interfacial water molecules, thereby enhancing the kinetics of HER and hydrogen oxidation reactions (HOR).…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids have highly tunable ion structures, high intrinsic conductivity, wide electrochemical windows, and can be designed to be proton donors or acceptors. 30–33 These properties provide many avenues for using ionic liquids as co-catalytic promoters in electrocatalysis. Further, ionic liquids are soluble in nonaqueous and aprotic solvents, circumventing competing water reduction and providing opportunities for detailed mechanistic study of proton-coupled electron transfers in electrochemical CO 2 reduction by introducing external proton donors.…”
Section: Introductionmentioning
confidence: 99%